(untitled) (Comparative Professional Pedagogy, 2021)
The paper is aimed at studying “Integrated Design” Master’s degree program at Köln International School of Design (KISD) that is a part of Cologne University of Applied Sciences. The program offers project- and student-oriented study in inspiring and contextualized environment that is suitable for implementing problem-solving practices and techniques and provides students with high level of flexibility and independence. The key component of the program is the completion of the thesis within one of the thematic sections: Urban Intensity and Resources, Material Systems and Laboratory Culture, Social and Public Innovations, and Visual Culture and Politics. Curriculum of the program has been thoroughly studied and it has been defined that the duration of the program is 3 semesters. During the first semester, students develop their vision and explore issues related to the thematic section that they have chosen for thesis writing and have 3 types of courses: 1) KISD short-termed, medium-termed and long-termed projects and scientific seminars; 2) courses with master-classes (MethodLab, Design Approaches, Mentoring); 3) courses with students of the same thematic section. During the second semester, they start their designing process and apply observation, exploration, experimentation and practical designer work to deal with their thesis. The third semester is dedicated to in-depth work on the thesis and its presentation. It has been determined that the curriculum of the “Integrated Design” program presupposes 90 ECTS credits for the whole study with 30 credits for each semester. Each semester includes compulsory modules the completion of which is verified by module examinations. Curriculum provides information on the quantity of credits attributed to each module, to Master’s thesis and final exam which is actually the defense of the thesis. The procedure of assessing the exam has been described and the calculation of the final exam cumulative grade has been outlined. Students complete Master’s degree program if they obtain 90 ECTS credits. The requirements for their obtaining have been characterized in the paper.